Pseudomonas aeruginosa Lipopolysaccharide Involves in Inflammatory and Autoimmune Response in Patients with Rheumatoid Arthritis (World Journal of Experimental Biosciences, 2022)
Rheumatoid arthritis (RA) is one of the complex diseases caused by unknown reasons and mechanisms of action of the disease. Studies that address the role of bacterial antigens in stimulating the inflammation, autoimmune response, and activity of RA are scanty in the literature. Therefore, the current review attempts to highlight autoimmune diseases’ pathogenicity, especially RA. The review also focused on the role of bacterial infections and lipopolysaccharides in stimulating the autoimmune response as well as the activity of RA. The study showed that Pseudomonas aeruginosa LPS increased the inflammation response and activity of RA. Moreover, this review showed the effect of this LPS on increasing the autoimmune response in patients with RA. The study concluded the role of bacterial infection and bacterial LPS in the autoimmune response phenomenon in the laboratory as well as RA disease activity, and inflammation immune response.